A dimensão política das interações comunicativas em papo de polícia: cenas disscaso e reconfigurações do mundo comum - Thales Vilela Lelo (2015)
This research has as nodal question the tensions involved in the reciprocal construction of subjects as partners in a communicative scene, and the challenges imposed in a research that leaning in grasp the process of building and settling these scenes, taking, as starting point, a cultural product of media. The empirical object of reference is the first season of the series Papo de Polícia, consisting in seven episodes that were broadcasted in Multishow channel in 2011. The protagonist of this program is the civil policeman Roberto Chaves, who was invited to the "challenge" of staying seven days in the Complexo do Alemão (RJ) in order to report, through a video diary, the experiences on that site and the interaction with the locals. The plot takes, as backdrop, the historically conflicting interactions between police and slum dwellers, and will be the aim of this work discover how the contact between the subjects in the series may or may not generate controversy scenes of enunciation in which the potential construction of subjects as interlocutors (and not as enemies) puts in relation worlds that are tangent and repellent. The tone of these scenes concerns the conditions in which the dialogue partners can be recognized as "beings of word." Recognize the other as a partner involves considers it as an artificer of a shared common world. Thus, this research initially will understand the concepts of "common" that support the device of Papo de Polícia and narrow ties with ways of understanding the communicative practices, perceived as "action in common". Then, the implications of this "relational" address of communication will be contrasted with another way to realize the "common" inherent in interactional processes: a fractured common, splitted between the assumptions that govern a mutually referenced action (which assumes mutual understanding and certain equality of understanding), and the ways of distribute the terms of common that hierarchize the bodies and even engulf their gaps under the ideal of a supposed alliance between partners. Under this set of conceptual assumptions, the analysis will address the Papo de Polícia images: what they ask to the viewer? Step into the landscape opened for this question will require the formulation of operators which will "open the eyes" for their elements in its discursive and expressive aspects. In incursion into the program, will be pointed out different ways to take the road of the images left by him and the interactions that shape your scenes: on the one hand, it should take notice of the manifestations of "communion" between police and residents of Complexo do Alemão throughout the series; at the other, the destabilizations to this frame that emerge in times when the device configured for the season is provisionally splitted. It will be realize that in such occasions becomes possible to put in overhead and even under verification the "common" that hitherto formed the basis of interactions in plot.